THE EFFECT OF SERVICE AND PRODUCT QUALITY ON THE DECISION TO BECOME A MEMBER OF BMT UGT SIDOGIRI CAPEM WARU - Fitria Ayu Lestari Niu; Ulfa Maqfiroh (IAIN Manado, 2022)
This study aims to determine the effect of service and product quality on the decision to become a member of BMT UGT Sidogiri Capem Waru partially and simultaneously by using a descriptive quantitative approach. Data was obtained by distributing questionnaires to respondents. The results of this study found that partially the service quality has no effect on member decisions with a significance level of 0.842 > 0.05. Meanwhile, product quality has a positive and significant influence on decision-making to become a member. Simultaneously service and product quality influence the decision to become a member by 27.1%, while other variables outside of this study influence the remaining 72.9%. Service quality did not affect the decision to become a member caused of the lack of responsiveness of employees in responding to member the complaints, the lack of sensitivity of employees to the intentions of prospective members, and the lack of active employees in introducing and socializing the Mobile application (BMT UGT Nusantara). Meanwhile, product quality has a significant influence caused the products run by BMT UGT Sidogiri Capem Waru are following sharia principles, both product submission requirements and profit-sharing ratios where this product can reach various levels of various professions of society such as farmers, traders, private employees, civil servants, and students.